Determination of the maximum force due to skull impact in fights between sheep of the Ovis aries species - Felisberto, L. C.; Ruffino, R. T. (Wit Press, 2002)
The present article presents a means of determining the maximum impact force between two bodies from the determination of the involved impulse in the impact and the sound emitted by the shock of the bodies during this impact.It also presents a case study applied to the shock between the skulls of male sheep of the Ovis aries species. These animals do not possess horns and dispute the territorial leadership by fighting, during which the skull is used as a weapon of attack, similar to a battering ram.Initially, a revision of basic physics approaching the theory of impulse is made, which shows that the average force during an impact can be obtained by the quantity of movement of the bodies. In its turn, the quantity of movement is obtained through the average speed of approach and the mass of the bodies. The maximum force is obtained from the average force, using the approach of the Force X Time curve with the Sonorous Intensity X Time Curve.In order to study the case of a shock between two sheep, the mass of the bodies was obtained through direct weighing and the average speed of approach obtained indirectly through filming, thus making possible the calculation of the average force. The Sonorous Intensity X Time Curve was obtained through the recording of the sound of the impact during a filmed fight, with later manipulation through computer programs. With this data the maximum force exercised between the skull of the sheep during the impact was obtained, which will be used in later studies.